Characterization of biochar derived from rubber wood sawdust through slow pyrolysis on surface porosities and functional groups - Se, Sian Meng; Shaaban, Azizah; Mitan, Nona Merry Merpati; Dimin @ Mohd Amin, Mohd Fairuz (Elsevier Ltd., 2013)
Biochars were prepared by conducting slow pyrolysis of rubber wood sawdust (RWSD) derived from sawn timber. Eventhough researches on preparation of biochar from biomass have been reported by many researchers, limited work has been reported for investigation of biochar RWSD for its surface porosities and functional groups. Surface porosity of biochars provides a suitable dimension for cluster of microorganism to grow and higher porosity for better water holding capacity. Surface functional groups contain oxygen may help to improve the soil fertility by increasing the cation and anion exchange capacities to reduce the nutrient leaching in soil. The pyrolysis process was carried out at temperatures ranging between 300 °C to 700 °C at the heating rate of 5 °C/min for 3 hours with continuous nitrogen purging. The influence of pyrolysis temperatures on the biochars pores were investigated by using X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) surface analysis and Scanning Electron Microscopy (SEM). The surface functional groups were examined by Fourier Transform Infrared (FT-IR). SEM analysis clearly showed the development of well-defined pores distributed on biochars surface. It was found that the maximum BET surface area and total pore volume were 5.493 m2/g and 0.0097 cm3/g respectively for biochar pyrolysis at 700 °C. The FT-IR spectrum analysis showed the functional groups decreased with the increasing of pyrolysis temperature. The results highlighted the effect of pyrolysis temperature on biochar pores accumulative that associated with soil fertility and nutrient retention in soil which could be beneficial to the agricultural industries.